Resolution components and lipid metabolism as emerging targets in neurodegeneration - Salvador, Gabriela Alejandra (2024)
Neurodegenerative disorders are characterized by the progressive and selective loss of vulnerable neurons in specific brain areas. Some major harmful challenges associated with neuronal dysfunction and death are proteotoxicity, oxidative stress, and neuroinflammation. By using metabolomics, we detected that phospholipids are selectively hydrolyzed in astrocytes and neurons by several phospholipases A2 in response to toxicity threats. In addition, ferroptosis- associated stimuli produced an imbalance in arachidonic acid (AA) and docosahexaenoic acid (DHA) content. This fatty acid rewiring activated AA- and DHA-dependent resolution pathways to mitigate pro-inflammatory signaling, and lipid droplet accumulation thus promoting cell survival. The inflammation/resolution balance is governed by many specialized pro-resolving lipid mediators acting as ligands of the GPCR receptor FPR2/ALX. In line with this, we also demonstrated that neurons and astrocytes secrete lipid ligands for FPR2/ALX-mediated resolution. Proteotoxic stimulus and oxidative stress also triggered lipid droplet accumulation in neurons and glia. Active lipid droplet hydrolysis and free cholesterol accumulation are associated with gliosis and movement disorders when massive dopaminergic neuronal death occurs in mice midbrain. Thus, depending on the neuronal injury level, lipid droplets can act as protective against damage or as promoters of cellular death. We hypothesize that lipid droplets act as yin/yang effectors of neurodegeneration working as dynamic fatty acid donors or sinks to intervene in resolution or pro-inflammatory signaling. Our results shed light on new targetable metabolic pathways for treating neurodegenerative disorders.